Project Based Learning in Hospitality Education: Aristotle's Realism Perspective in Educational Philosophy - Arifah, Khafidhta Qudsiana Nurul; Wiratmoko, Gandung Aulia; Fauziati, Endang; Maryadi (International Journal of Educational Research Excellence (IJERE), 2023)
The aim of this study is Project Based Learning with philosophy realism in Hospitality Education. This study is qualitative descriptive literature research. This article discusses about philosophy education realism in informal education for practice or Project Based Learning. In this study, researchers take Project based Learning, namely training / coaching for hotel workers candidate. The results of this research show the approach Project Based Learning is not only facilitate learning holistic based on the actual projects, but also deliver experience practical for students as the emphasized by Aristotle in his theory It is emphasized understanding through action. This article presents strong argument of integration Aristotle's philosophy in learning context, and creating correlation between theory and practice as well as in preparing student for facing demands of the actual world of hospitality industry.